Aristolochia trilobata: Identification of the Anti-Inflammatory and Antinociceptive Effects - Dayana da Costa Salomé; Natália de Morais Cordeiro; Tayná Sequeira Valério; Darlisson de Alexandria Santos; Péricles Barreto Alves; Celuta Sales Alviano; Daniela Sales Alviano Moreno; Patricia Dias Fernandes (Biomedicines, 2020)
Aristolochia trilobata, popularly known as “mil-homens,” is widely used for treatment of stomach aches, colic, asthma, pulmonary diseases, diabetes, and skin affection. We evaluated the antinociceptive and anti-inflammatory activities of the essential oil (EO) and the main constituent, 6-methyl-5-hepten-2-yl acetate (sulcatyl acetate, SA). EO and SA (1, 10, and 100 mg/kg, p.o.) were evaluated using chemical (formalin-induced licking) and thermal (hot-plate) models of nociception or inflammation (carrageenan-induced cell migration into the subcutaneous air pouch, SAP). The mechanism of antinociceptive activity was evaluated using opioid, cholinergic receptor antagonists (naloxone and atropine), or nitric oxide synthase inhibitor (L-NAME). EO and SA presented a central antinociceptive effect (the hot-plate model). In formalin-induced licking response, higher doses of EO and SA also reduced 1st and 2nd phases. None of the antagonists and enzyme inhibitor reversed antinociceptive effects. EO and SA reduced the leukocyte migration into the SAP, and the cytokines tumor necrosis factor and interleukin-1 (TNF-α and IL-1β, respectively) produced in the exudate. Our results are indicative that EO and SA present peripheral and central antinociceptive and anti-inflammatory effects.